A homeopatia no sus - Camilo, Lujani Aparecida [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
This study is based on the perspective that Homeopathy is a medical practice that seeks the integrative cure of patients where physical, emotional and psychological conditions are all important. Motivations of SUS (Brazilian Public Health System) patients who deliberately engaged in Homeopathy treatments were searched within the structure of UNESP Clinical Hospital of Botucatu, São Paulo, Brazil. The qualitative method of “DSC” to gather information obtained from patients and to proceed analyses was used

Esse estudo é embasado na perspectiva de que a homeopatia está consolidada em uma prática médica, a qual visa a cura através da percepção integral do individuo ao se importar com as condições físicas, emocionais e psicológicas na promoção da saúde. Diante disso, buscamos compreender quais seriam as motivações de pacientes do Sistema Único de Saúde (SUS) da rede do Hospital das Clínicas da Unesp de Botucatu, que os fizeram optar pelo tratamento homeopático, utilizando uma abordagem qualitativa baseada na metodologia do Discurso do Sujeito Coletivo (DSC)
Keywords: Homeopatia - Avaliação; Sistema Único de Saúde (Brasil) Tratamento homeopático